State of the World's Plants 2017 - Willis, Kathy (Royal Botanics Gardens Kew, 2017)
A detailed knowledge of plants is fundamental to human life on Earth. Plants underpin all aspects of our everyday life - from the food that we eat, to the clothes that we wear, the materials we use, the air we breathe, the medicines we take and much more. These essential services provided by plants are far too often taken for granted. This is the second annual report in which we have scrutinised databases, published literature, policy documents, reports and satellite imagery to provide a synthesis of current knowledge on the world's plants.